((3y+4)*2)+((y+3)*2)=70

Simple and best practice solution for ((3y+4)*2)+((y+3)*2)=70 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((3y+4)*2)+((y+3)*2)=70 equation:


Simplifying
((3y + 4) * 2) + ((y + 3) * 2) = 70

Reorder the terms:
((4 + 3y) * 2) + ((y + 3) * 2) = 70

Reorder the terms for easier multiplication:
(2(4 + 3y)) + ((y + 3) * 2) = 70
((4 * 2 + 3y * 2)) + ((y + 3) * 2) = 70
((8 + 6y)) + ((y + 3) * 2) = 70
(8 + 6y) + ((y + 3) * 2) = 70

Remove parenthesis around (8 + 6y)
8 + 6y + ((y + 3) * 2) = 70

Reorder the terms:
8 + 6y + ((3 + y) * 2) = 70

Reorder the terms for easier multiplication:
8 + 6y + (2(3 + y)) = 70
8 + 6y + ((3 * 2 + y * 2)) = 70
8 + 6y + ((6 + 2y)) = 70
8 + 6y + (6 + 2y) = 70

Remove parenthesis around (6 + 2y)
8 + 6y + 6 + 2y = 70

Reorder the terms:
8 + 6 + 6y + 2y = 70

Combine like terms: 8 + 6 = 14
14 + 6y + 2y = 70

Combine like terms: 6y + 2y = 8y
14 + 8y = 70

Solving
14 + 8y = 70

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 8y = 70 + -14

Combine like terms: 14 + -14 = 0
0 + 8y = 70 + -14
8y = 70 + -14

Combine like terms: 70 + -14 = 56
8y = 56

Divide each side by '8'.
y = 7

Simplifying
y = 7

See similar equations:

| .5n+15=3n | | (X+5)(x+5)-49=0 | | -12=w+18 | | 5z-18-z+2= | | 10=(2*6)-8 | | 2x-3x-10=-9 | | B-2b=b+4b+2 | | 3(y-4)= | | 4x+8/4-2=x | | 2x^2-4x/x-2 | | 8+7x+4x=63 | | x+6=x.4 | | 99x+65=-4x | | z(4x^10y^11z^8)= | | 7+3C=-7 | | .25n=2n-21 | | 5(2x-12)+21=2x+21 | | w=4x(y-5) | | 210(-3)= | | 2(3+x)=20+3x | | 9y+2=11y+8 | | z(16xy^3z^3)= | | e^4y-ln(y^2+3)=2x | | Yy-2=y+1y-5 | | 27x^2-54x+2805=0 | | x+8=-2-2+5x | | 2w-4=2 | | 2w-4= | | k=11+9-8+99 | | -6x+8=6x+8 | | 17+b= | | log(5*3)= |

Equations solver categories